Preliminary Investigations into Tris(2,2'-bipyridyl) Ruthenium (III) as a Chemiluminescent Reagent for the Detection of 3,6-Diacetylmorphine (Heroin) on Surfaces - Agg, K.; Barnett, N.; Lewis, Simon; Pearson, J. (Blackwell Publishing, 2007)
The use of tris(2,2'-bipyridyl) ruthenium (III) as a chemiluminescent spray reagent spot-test for heroin is discussed. Two forms of the reagent are investigated an aqueous and an anhydrous where both were found to give vastly different results. The aqueous reagent giving slow, low intensity chemiluminescence whilst the anhydrous reagent gave a fast, bright response in the presence of 3,6-diacetylmorphine. The anhydrous reagent is less sensitive the slow, intensity response is characteristic of only two opiates tested 3,6-diacetylmorphine and 3-monoacetylmorphine.